A student guide to equity and equitable remedies in Malaysia - Ali, Zuraidah; Syed Abdul Kader, Sharifah Zubaidah; Mohamad, Nor Asiah; Hamzah, Hamimah (Lexis Nexis, 2016)
This book can be used in other law schools offering the Bachelor of Laws programme such as UM, UiTM, UKM, UNiSZa, UUM, USIM, MMU and Taylors University. All law students who are reading law in Malaysia will have to undertake the core subject of Equity and Trust. It is also useful as a source of reference to law schools outside Malaysia and other members with legal background in all sectors, locally or at the international front, as it offers a use preliminary insight on how equitable remedies and relief work in Malaysia.